Optimising of processing parameters of Titanium alloy foams using Taguchi method for improved electrical conductivity - Ahmad, S.; Muchtar, A.; Muhamad, N.; Sahari, J.; Jamaludin, K. R.; Ibrahim, M. H. I. (2009)
Metal foam has many beneficial physical and mecchanical properties. These properties are from high im pact energy absorption, high stiffness and strength to weight ratios, high gas permeability, and finally to high therm al conductivity. There arc several applications o f open-celled metal foam which arc widely used as light weight constructional materials, architectural materials, impact absorbers, silcncers, filters, heat exchangers and implants. Metal and metal alloy foams containing up to 95% porosity are being explored for many applications. T hey offer m any potential benefits for components that operate in extreme environments and at temperatures where conventional polym eric foams cannot be used (D egischer & Kriszt 2002). T hey also prom ise cost advantages over conventional light weight honeycomb structures and rib-stiffened panels used in m any aerospace and ship structures (Torn 2007).